A dynamic flow‐chamber‐based adhesion assay to assess canine platelet–matrix interactions in vitro. (29th April 2013) - Ferkau, Annika; Ecklebe, Silke; Jahn, Kira; Calmer, Simone; Theilmeier, Gregor; Mischke, Reinhard
<x xml:space="preserve">Abstract</x> Background Dynamic adhesion assays allow the examination of platelet dysfunction and drug effects on platelet function. Objective The purpose of the study was to optimize several parameters such as type and concentration of collagen, wall shear stress, and the concentration of the platelet‐activating agonist in a new biochip perfusion chamber for the study of canine platelets. Methods After fluorescent staining of platelets, citrated blood of 10 healthy dogs was perfused through the flow chamber coated with different concentrations of canine or bovine skin collagen. Wall shear stress ranged from 14 to 60 dynes/cm2. Protease‐activating receptor 4 (PAR 4) agonist was used for platelet activation. After perfusion, platelet attachment to the collagen matrix was quantified based on fluorescent imaging. Total platelet covered area and average size of platelet covered areas were measured by planimetry. Results Canine platelet adhesion was supported by ≥ 200 μg/mL canine collagen, but not bovine skin collagen. Consistent results were obtained with a wall shear stress of 14 dynes/cm2, whereas higher wall shear stress resulted in increased variability. Platelet activation with PAR 4 agonist increased the total platelet covered area and the average size of platelet covered areas. Conclusions This study indicates the need to carefully select collagen type and concentration to assess canine thrombus formation in a dynamic flow chamber. The established method should be a useful tool to determine changes in platelet–matrix interactions as an indicator of platelet activation or platelet dysfunction in dogs.